Subsidizing Agricultural Production on Imperfect Markets (The Pakistan Development Review, 1987)
Economic growth, and the distribution of wealth and income, are two of the major, dimensions of economic policy in all countries. If one follows the data published by the World Bank, one can see, that even the relative income distribution in the developed and some of the developing countries are very similar; it is only, that the level of income is much lower in the latter countries, and therefore, that low income is more visible and striking. Therefore, raising the level of income of the very poor has been a major task of all governments. There has been a very controversial discussion, however, as to how the incomes of the poor can be raised easily, whether by economic growth, redistribution of wealth, i.e. the means of production, or of income. This discussion has been inconclusive so far, and the present paper sets out to examine some of these aspects. Pakistan may serve as a perfect example, considering the fact, that the country first suffered from an overemphasis on economic growth and a neglect of distribution and then tried distribution with no growth.